2022
DOI: 10.3390/molecules27185789
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Anti-Influenza Virus Activity and Chemical Pattern Recognition to Explore the Quality Evaluation Method of Lonicerae Japonicae Flos

Abstract: Lonicerae japonicae flos (LJF, Lonicera japonica Thunb.) is adopted as a core herb for preventing and treating influenza. However, the anti-influenza virus components of LJF and the impact of quality-affecting factors on the anti-influenza activity of LJF have not been systematically investigated. In this study, a strategy integrating anti-influenza virus activity, ultrahigh-performance liquid chromatography fingerprint and chemical pattern recognition was proposed for the efficacy and quality evaluation of LJ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…LJF extract has been shown to not only reduce levels of IL-6 and TNF-α in order to reduce the inflammatory response but also to combat viral importation and replication by attenuating SARS-CoV-2 M pro activity [ 26 ]. Furthermore, LJF is regarded as a core anti-influenza herb, and its key chemical components against the influenza virus have been identified as neochlorogenic acid, chlorogenic acid, and cryptochlorogenic acid [ 27 ]. The repair rate of the lung index and the improvement rate of IL-6 and IFN-γ were chosen as the evaluation indexes of drug efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LJF extract has been shown to not only reduce levels of IL-6 and TNF-α in order to reduce the inflammatory response but also to combat viral importation and replication by attenuating SARS-CoV-2 M pro activity [ 26 ]. Furthermore, LJF is regarded as a core anti-influenza herb, and its key chemical components against the influenza virus have been identified as neochlorogenic acid, chlorogenic acid, and cryptochlorogenic acid [ 27 ]. The repair rate of the lung index and the improvement rate of IL-6 and IFN-γ were chosen as the evaluation indexes of drug efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Chlorogenic acid has a broad spectrum of antiviral activity and could inhibit RSV infection by modulating the expression of TLR3, TBK1, and IRF3 in the TLR3 signaling pathway and decreasing the level of IFN-β [ 11 ]. Secoxyloganin plays an important role in the antiviral activity of LJF and may be related to the synergistic effect of multiple compounds [ 27 ]. This was in agreement with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional Chinese herbs are gaining attention as promising complementary and alternative therapies to fight infections [ 27 ]. LJF has been used for many years in China for its efficacy in the treatment of bacterial and viral infections, as documented in Mingyi Bielu [ 8 , 9 , 28 ]. LJF was the most popular traditional Chinese medicine used in treatments of severe acute respiratory syndromes (SARS) and influenza A in 2003 and 2009 [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research by Gao et al [ 30 ] showed that LJF extracts exerted protective effects against Hydroquinone-induced cytotoxicity in hepatic L02 cells. Xie et al [ 9 ] explored the quality evaluation method of LJF by combining anti-H1N1 activity with chemical pattern recognition, which is of great significance for ensuring the clinical effect of LJF antiviral. Zeng et al [ 6 ] reviewed several anti-RSV efficacies of LJF.…”
Section: Discussionmentioning
confidence: 99%
“…Medicinal components have also been characterized. In the flowers, neochlorogenic acid, chlorogenic acid, cryptochlorogenic acid, 4,5- O -caffeoylquinic acid, sweroside and secoxyloganin have been found [ 15 ]. In the leaves, luteolin, rutin, luteoloside, lonicerin, isochlorogenic acid C, isochlorogenic acid B, isochlorogenic acid A and chlorogenic acid have been found [ 16 ].…”
Section: Introductionmentioning
confidence: 99%